Combined antenna for a mobile system of radioacoustic sounding - Ulyanov, Y. N.; Misajlov, V. L.; Vetrov, V. I. (Видавництво Національного університету "Львівська політехніка", 2009)
Combined radar-acoustic horn-reflector antenna has been developed for a mobile radioacoustic and acoustic sounding system. The antenna beamwidths at acoustic and electromagnetic waves are equal. The system works according to the inclined radioacoustic method (IRAS) and is intended for measuring profiles of temperature, wind and atmospheric turbulence intensity at the heights of about 500 m.
Keywords: radioacoustic system; combined antenna; inclined sounding